2007
DOI: 10.1017/s0022215107006482
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus prevalence in laryngeal squamous cell carcinoma

Abstract: In our series, a very low human papilloma virus prevalence was found among laryngeal squamous cell carcinoma cases. The human papilloma virus genotypes detected were mostly 6 and/or 11, and 16 in only one case. To the best of our knowledge, this is the first report of human papilloma virus prevalence in laryngeal squamous cell carcinoma, based on polymerase chain reaction genotyping in a Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 16 publications
1
31
1
7
Order By: Relevance
“…The laryngeal papilloma is not immediately apparent and may be quite difficult to diagnose until they become symptomatic. The HPV genotypes most often found in laryngeal papilloma were HPV6 and 11 [45-47]. Thus, preventing HPV6 and HPV11 infection can reduce the incidence of genital warts.…”
Section: Discussionmentioning
confidence: 99%
“…The laryngeal papilloma is not immediately apparent and may be quite difficult to diagnose until they become symptomatic. The HPV genotypes most often found in laryngeal papilloma were HPV6 and 11 [45-47]. Thus, preventing HPV6 and HPV11 infection can reduce the incidence of genital warts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cervical carcinomas from 2118 patients showed that the eight most common high-risk types were HPV16 (50%), HPV18 (17.8%), HPV58 (16.3%), HPV33 (8.7%), HPV52 (6.8%), HPV39 (3.0%), HPV45 (2.5%), and HPV31 (2.3%) (43). In addition, several studies have reported HPV double infections in 14.3% of recurrent respiratory papillomatosis (44) and 7.6% of laryngeal squamous cell carcinoma (45). Using microarray analysis to evaluate HPV infection in women with and without cervical dysplasia, double infections were detected in 13%, but multiple infections occurred significantly more often in CIN-positive samples compared with in controls (45% vs. 23%) (46).…”
Section: Discussionmentioning
confidence: 99%
“…22 Ül ke miz de 1998 yı lın da ya pı lan bir ça lış ma da in si tu hib ri di zas yon tek ni ği ile la rink sin pa pil lomla rı, pre kan se röz lez yon la rı ve kan ser le rin de HPV DNA araş tı rıl mış ve sku a möz hüc re li kar si nom olgu la rın da HPV DNA po zi tif li ği %69.2 ola rak tes pit edil miş tir. 6 Di ğer bir ça lış ma da ise 21 la rinks ve 26 ak ci ğer kar si no mun da HPV DNA var lı ğı in si tu hib ri di zas yon tek ni ği ile araş tı rıl mış ve HPV DNA po zi tif lik ora nı sı ra sıy la %47.6 ve %11.5 ola rak bulun muş tur. 7 Türk po pü las yo nun da la rinks kar sinom lu has ta lar da HPV sık lı ğı nı tes pit et mek için PZR tek ni ği kul la nı la rak 99 has ta üze rin de ya pıl -mış bir ça lış ma da HPV DNA pre va lan sı %7.36 olarak sap ta nır ken, tes pit edi len HPV ge no tip le ri tip 6, 11 ve 16 ola rak kay de dil miş tir.…”
Section: Tar Tiş Maunclassified
“…4,5 Ül ke miz de üst so lu num yo lu kan ser le rin de bu vi ru sun be lir len me si ve ge no tip len di ril me si ne yö-ne lik sı nır lı sa yı da ça lış ma ya rast lan mış tır. [6][7][8] Gün-gör ve ar k. nın 99 has ta üze rin de yap tık la rı bir ça lış ma da HPV DNA pre va lan sı %7.36 ola rak sapta nır ken, tes pit edi len HPV ge no tip le ri tip 6, 11 ve 16 ola rak kay de dil miş tir. 6 Ül ke miz de ya pı lan di ğer bir ça lış ma da in si tu hib ri di zas yon tek ni ği ile larink sin pa pil lom la rı, pre kan se röz lez yon la rı ve kan ser le rin de HPV DNA araş tı rıl mış ve sku a möz hüc re li kar si nom ol gu la rın da HPV DNA po zi tif li ği %69.2 ola rak tes pit edil miş tir.…”
unclassified
See 1 more Smart Citation